Power system monitoring and control - Bevrani, Hassan; Watanabe, Masayuki (Electrical engineer); Mitani, Yasunori; Books24x7, Inc. (Hoboken, N.J. : John Wiley & Sons, 2014)
"Power System Monitoring and Control presents a comprehensive overview of the basic principles and key technologies for the monitoring, protection, and control of contemporary wide-area power systems. Provides an updated and comprehensive reference for researcher and engineers working on wide-area power system monitoring and control (PSMC); Links fundamental concepts of PSMC, advanced metering and control theory/techniques, and practical engineering considerations; Covers PSMC problem understanding, design, practical aspects, and timely topics such as smart/microgrid control and coordinated voltage regulation and angle oscillation damping. Incorporates authors' experiences teaching and researching in various international locales including Japan, Thailand, Singapore, Malaysia, Iran, and Australia." --
Title from title screen.
.
Includes bibliographical references and index.
Text.
Available also in a print ed.
Mode of access: Internet via World Wide Web.
Keywords: Electric power systems -- Control; Electronic books; Electronic books